Fanthropologies (Minneapolis : University of Minnesota Press, 2010)
- The art of cute little things : Nara Yoshitomo's parapolitics / Marilyn Ivy ##- Transforming U.S. anime in the 1980s / Brian Ruh ##- Speciesism, part II : Tezuka Osamu and the multispecies ideal / Thomas Lamarre ##- Undoing inter-national fandom in the age of brand nationalism / Koichi Iwabuchi ##- World and variation : the reproduction and consumption of narrative / Ōtsuka Eiji ##- Frenchness and transformation in Japanese subculture, 1972-2004 / Anne McKnight ##- Monstrous media and delusional consumption in Kon Satoshi's Paranoia agent / Gerald Figal ##- Lucid dreams, false awakenings : figures of the fan in Kon Satoshi / Kerin Ogg ##- Cosplay photography sampler / Eron Rauch and Christopher Bolton ##- Dark energy : what fansubs reveal about the copyright wars / Ian Condry ##- Akihabara : conditioning a public "otaku" image / Patrick W. Galbraith ##- Comic market : how the world's biggest amateur comic fair shaped Japanese Dōjinshi culture / Fan-Yi Lam ##- Suffering forces us to think beyond the right##- left barrier / Amamiya Karin ##- Fans behaving badly : anime metafandom, brutal criticism, and the intellectual fan / Kathryn Dunlap and Carissa Wolf ##- Anatomy of permutational desire : perversion in Hans Bellmer and Oshii Mamoru / Livia Monnet ##- A cocoon with a view : hikikomori, otaku, and Welcome to the NHK / Marc Hairston ##- Reorganizations of gender and nationalism : gender bashing and loliconized Japanese society / Naitō Chizuko ##- Aeryn's dolls / Jin C. Tomshine ##- Review and commentary.
boek